Perancangan Sistem Informasi Penjualan Meubel Berbasis E-Commerce Pada Aisyah Meubel Jati Ukir - Adinda Bidadari; Fikri Hamidy (CHAIN: Journal of Computer Technology, Computer Engineering, and Informatics, 2023)
E-commerce Furniture Sales Information System at Aisyah Meubel Jati Ukir Bandar Lampung is a research that aims to design and implement an e-commerce-based furniture sales information system that allows Aisyah Meubel Jati Ukir to expand market reach and increase efficiency in managing product sales their furniture. This research uses a software development method with stages of needs analysis, system design, implementation and testing. This information system allows customers to browse the furniture product catalogue, place orders online, and make payments via a secure e-commerce platform. Additionally, store owners can easily manage product stock, manage customer orders, and track sales in real-time. The results of this research show that the implementation of an E-commerce Based Furniture Sales Information System at Aisyah Meubel Jati Ukir Bandar Lampung provides significant benefits, such as increasing customer access and efficiency in the sales process. The tests that have been carried out for the experimental side of ISO 25010 obtained a score of 100% in the functional suitability test which went as expected. Meanwhile, usability testing in the case study achieved a score of 92% and usability for students was 92.5% based on the Strongly Agree criteria.